Dekonstruksi Nilai Karakter Sastra Anak Berjenis Fabel dalam Buku Tematik Kelas II Tema Kebersamaan - Yenicke Bara Nurdyana (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study was conducted to analyze the value of character education in the fable story at the second grade thematic student book with the theme Kebersamaan and to describe the result deconstruction of the character education values in the student’s book fable story. The type of research is library research. The research was conducted on textbooks of second grade thematic teaching material. The goal is analyzing the contents of the book. The indicators are used to determine the contents of the book, and the final goal is to know the result of the analysis the contents of the book. The result of the research is that children’s literature at the second grade thematic student books with the theme Kebersamaan contains the value of character education, has a dominant text and a reversal of the dominant text which shows the existence of marginalized moral messages.